The Role of Digital Technology in Improving Learning Outcomes: A Literature-Based Analysis - Arisanti, Rica (PPSDP International Journal of Education, 2025)
This literature-based study examines the effectiveness of technology integration in education to improve student learning outcomes. Drawing from a wide range of scholarly sources, the study highlights how technological tools such as multimedia applications, e-learning platforms, and augmented reality enhance cognitive development, engagement, and critical thinking. While digital technology offers substantial benefits, the effectiveness of its implementation depends on factors such as teacher competency, infrastructure, and learning design. The study concludes that strategic, student-centered, and contextually relevant use of technology is essential for maximizing learning outcomes.